DIGITAL TRANSFORMATION IN THE MINISTRY OF THE INTERIOR: FUTURE CHALLENGES. THE SECURITY TECHNOLOGY CENTRE (CETSE) - Belda Esplugues, Enrique (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
As a part of the functions entrusted to the Deputy Direction General of Communication and Information Systems for Security (SGSICS) of the Secretary of State for Security of the Ministry of the Interior, there is the direction of the Security Technology Centre (CETSE), from which multiple technological and digital transformation initiatives are promoted in order to serve as support tools for the mission carried out by the State Security Corps and Forces to safeguard the rights and freedoms of citizens, as well as the Ministry of the Interior itself in the fulfilment of their functions. The CETSE has become a digital reference centre, ideal for attracting technological excellence and providing the Ministry of the Interior with the capacity for innovation in the field of security technologies. Today, the Security Technology Centre (CETSE) is a reality that manages more than 100 projects. Thus, from this Centre, we can identify industrial sectors, investigate future trends and motivate stakeholders towards innovative technological actions.
Keywords: Tecnnology Centre; Public Security; Digital Transformation; Information and Communication Systems